The Influence of Environmental, Social, and Governance Performance Disclosure on Stock Performance - Novia, Novia; Adrianto, Fajri; Geraldina, Ira (Journal of World Science, 2024)
This research aims to evaluate the effect of environmental, social, and governance (ESG) performance disclosure on the stock performance of companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period, using the price earning ratio (PER) as an indicator of stock performance. The research population includes companies listed on the IDX with ESG scores from the Thomson Reuters Eikon Database during the period studied. The research sample of 190 companies was selected using a purposive sampling technique. The data analysis method used is Panel Data Regression Analysis with the help of STATA 14 for Windows software. The research results show that environmental performance partially has a positive and significant influence on stock performance, while social and governance performance has no significant influence. Simultaneously, environmental, social, and governance performance variables influence the company's stock performance. This research implies that companies on the IDX can improve their stock performance by paying attention to environmental performance aspects. Even though social and governance performance does not partially show a significant influence, attention to these three aspects can improve overall stock performance. These findings provide insight to practitioners, regulators, and investors regarding the importance of ESG disclosure in the context of the Indonesian capital market.